Enhancing Electrochemical Performance of Si@CNT Anode by Integrating SrTiO3 Material for High-Capacity Lithium-Ion Batteries - Nischal Oli; Diana C. Liza Castillo; Brad R. Weiner; Gerardo Morell; Ram S. Katiyar (Molecules)
Silicon (Si) has attracted worldwide attention for its ultrahigh theoretical storage capacity (4200 mA h g−1), low mass density (2.33 g cm−3), low operating potential (0.4 V vs. Li/Li+), abundant reserves, environmentally benign nature, and low cost. It is a promising high-energy-density anode material for next-generation lithium-ion batteries (LIBs), offering a replacement for graphite anodes owing to the escalating energy demands in booming automobile and energy storage applications. Unfortunately, the commercialization of silicon anodes is stringently hindered by large volume expansion during lithiation–delithiation, the unstable and detrimental growth of electrode/electrolyte interface layers, sluggish Li-ion diffusion, poor rate performance, and inherently low ion/electron conductivity. These present major safety challenges lead to quick capacity degradation in LIBs. Herein, we present the synergistic effects of nanostructured silicon and SrTiO3 (STO) for use as anodes in Li-ion batteries. Si and STO nanoparticles were incorporated into a multiwalled carbon nanotube (CNT) matrix using a planetary ball-milling process. The mechanical stress resulting from the expansion of Si was transferred via the CNT matrix to the STO. We discovered that the introduction of STO can improve the electrochemical performance of Si/CNT nanocomposite anodes. Experimental measurements and electrochemical impedance spectroscopy provide evidence for the enhanced mobility of Li-ions facilitated by STO. Hence, incorporating STO into the Si@CNT anode yields promising results, exhibiting a high initial Coulombic efficiency of approximately 85%, a reversible specific capacity of ~800 mA h g−1 after 100 cycles at 100 mA g−1, and a high-rate capability of 1400 mA g−1 with a capacity of 800 mA h g−1. Interestingly, it exhibits a capacity of 350 mAh g−1 after 1000 lithiation and delithiation cycles at a high rate of 600 mA hg−1. This result unveils and sheds light on the design of a scalable method for manufacturing Si anodes for next-generation LIBs.